The application of magnifying endoscopy in the diagnosis of cervical lesions - Qing Li; Jue Wang; Tao Sun; Hongwei Zhang; Limei Chen; Qing Wang; Long Sui; Keqin Hua (Heliyon)
Objective: This study aimed to assess the sensitivity and specificity of magnifying endoscopy in the examination of patients with high-risk factors for cervical lesions. Methods: Two equally skilled colposcopy specialists examined 59 patients admitted to the Obstetrics and Gynecology Hospital of Fudan University between March 14, 2023, and April 15, 2023. These patients underwent both colposcopy and magnifying endoscopy examinations. Preliminary diagnoses were then made by the two colposcopy specialists using colposcopy and magnifying endoscopy. The sensitivity and specificity of these methods were then evaluated compared to the postoperative pathology diagnosis for a better understanding of their efficacy. Results: Colposcopy exhibited sensitivity rates of 23.08 % for diagnosing normal tissue, 10 % for low-grade squamous intraepithelial lesions (LSIL), 90 % for high-grade squamous intraepithelial lesions (HSIL), and 84.62 % for cervical cancer, with specificity rates of 93.94 %, 67.35 %, 71.43 %, and 100 %, respectively. In contrast, magnifying endoscopy demonstrated sensitivity rates of 42.31 %, 40 %, 90 %, and 92.31 % for normal tissue, LSIL, HSIL, and cervical cancer, respectively. The corresponding specificity rates for these categories were 87.88 %, 77.55 %, 83.67 %, and 100 %. Conclusion: Magnifying endoscopy exhibits higher sensitivity and specificity compared to colposcopy in detecting cervical lesions. With the ability to magnify lesions up to 520 times, magnifying endoscopy facilitates precise visualization of cellular-level lesions, as well as associated anatomical features and vascular signals.